IMPLEMENTASI KEBIJAKAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN KALIJATI KABUPATEN SUBANG PROVINSI JAWA BARAT - Nur Handayani; Dede Risa Nurmayanti; Riant Nugroho (Jurnal Kebijakan Pemerintahan, 2021)
Abstract This study aims to determine how the implementation of integrated sub-district administrative services (PATEN) in Kalijati District, Subang Regency, West Java Province. The method used is a qualitative method with a descriptive approach. Informants were determined by the purposive sampling technique. Data were collected by using observation, interview, and documentation techniques. Analyzed through the stages of data reduction (data reduction), data presentation (data display), and conclusions drawing (verification). This study uses the policy implementation criteria of Donald van Metter and Carl van Horn which consists of 6 indicators. The results show that the implementation of the PATEN policy at Kalijati District is carried out quite well. It is evident from the 6 criteria that there are still things that need to be optimized. This can be seen (1) the criteria for the size and objectives of the policy are clear but need to be more informed, (2) the criteria for resources from the HR side need to increase discipline in terms of facilities resources, there needs to be an information board at the front office, (3) the criteria for the characteristics of implementing agents, (4) the criteria for the attitude or disposition of the implementers show a friendly, polite and good attitude but sometimes there are still delays, (5) the criteria for inter-organizational communication and implementing activities are that communication between organizations runs smoothly and is conducive because it refers to service standards determined and (6) the criteria of the economic, social and political environment are very supportive. Economically, it does not burden the community, even because of the openness in service and socially, the community feels facilitated by the PATEN policy. On this basis, it is necessary to optimize resources, both human resources such as increasing discipline and ability, both technical and functional, and supporting resources such as information boards. Keywords: Implementation, Policy, Service Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana implementasi pelayanan administrasi terpadu kecamatan (PATEN) di Kecamatan Kalijati Kabupaten Subang Provinsi Jawa Barat. Metode yang digunakan adalah metode kualitatif dengan pendekatan deskriptif. Informan ditentukan dengan teknik purposive sampling. Data dikumpulkan dengan teknik observasi, wawancara dan dokumentasi. Dianalisis melalui tahapan reduksi data (data reduction), penyajian data (data display), dan penarikan kesimpulan (conclusion drawing/ verification). Penelitian ini menggunakan kriteria Implementasi kebijakan dari Donald van Metter dan Carl van Horn yang terdiri dari 6 indikator. Hasilnya menunjukkan bahwa implementasi kebijakan PATEN di Kecamatan Kalijati terlaksana cukup baik. Terbukti dari 6 kriteria masih ada yang harus dioptimalkan. Hal ini terlihat (1) kriteria ukuran dan tujuan kebijakan jelas namun perlu lebih diinformasikan, (2) kriteria sumber daya dari sisi SDM perlu peningkatan kedisiplinan dari segi sumber daya sarana, perlu ada papan informasi di front office, (3) kriteria karakteristik agen pelaksana, (4) kriteria sikap atau kecenderungan (disposition) para pelaksana menunjukkan sikap ramah, sopan dan baik namun kadang masih ada yang terlambat, (5) kriteria komunikasi antar-organisasi dan aktivitas pelaksana bahwa komunikasi antar organisasi berjalan lancar dan kondusif karena mengacu pada standar pelayanan yang ditetapkan dan (6) kriteria lingkungan ekonomi, sosial dan politik sangat mendukung. Secara ekonomi tidak memberatkan masyarakat bahkan karena adanya keterbukaan dalam pelayanan dan secara sosial masyarakat merasa dimudahkan dengan adanya kebijakan PATEN. Atas dasar hal tersebut diperlukan optimalisasi sumber daya, baik sumber daya manusia seperti peningkatan kedisiplinan dan kemampuan baik teknis maupun fungsional dan sumber daya pendukung seperti papan informasi. Kata Kunci : Implementasi, Kebijakan, Pelayanan